Fundamentals of neuroanesthesia : a physiologic approach to clinical practice - Ruskin, Keith; Rosenbaum, Stanley H.; Rampil, Ira J. ([New York] : Oxford University Press, 2014)
This is a comprehensive guide to neuroanesthesia which focuses on neurophysiology, neuroanatomy, and neurosurgical procedures, and then offers practical approaches to the practice of neurosurgical anesthesia.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 10, 2014).
Keywords: Anesthesia; Anesthesia in neurology